Kesalahan Logis pada Teks Eksposisi Hortatori Siswa SMA N 54 Jakarta - Ni Ketut Pertiwi Anggraeni (Universitas Indraprasta PGRI Jakarta, 2020)
Logical Fallacies are the flaws that occur within an argument. Logical fallacies on hortatory exposition text happen because it involves invalid argument as the main point of this text. This research aims to discover types of logical fallacies that mostly found in hortatory exposition text written by the students of SMA N 54 Jakarta. This research took the logical fallacies from 80 texts written by the eleventh graders. Those logical fallacies were then classified into the classification of logical fallacies by Seyler. The result obtained were described using qualitative method with descriptive analysis as the main tool in interpreting the data. The result of this research discovered that begging the question is the type of logical fallacies that mostly found in the text of hortatory exposition of SMA N 54 Jakarta students.